The C allele of rs5743836 polymorphism in the human TLR9 promoter links IL-6 and TLR9 up-regulation and confers increased B-cell proliferation - Carvalho, Agostinho (2011)
In humans, allelic variants in Toll-like receptors (TLRs) associate with several pathologies. However, the underlying cellular and molecular mechanisms of this association remain largely unknown. Analysis of the human TLR9 promoter revealed that the C allele of the rs5743836 polymorphism generates several regulatory sites, including an IL-6-responding element. Here, we show that, in mononuclear cells carrying the TC genotype of rs5743836, IL-6 up-regulates TLR9 expression, leading to exacerbated cellular responses to CpG, including IL-6 production and B-cell proliferation. Our study uncovers a role for the rs5743836 polymorphism in B-cell biology with implications on TLR9-mediated diseases and on the therapeutic usage of TLR9 agonists/antagonists.